Enhancing Motivation and Students’ Learning Outcomes with Orang Kayo Hitam Comic in Physics Learning - Haerul Pathoni; Qodariah Barkah; Alrizal Alrizal; Wella Meliza; Louisiana Muliawati (Jurnal Ilmiah Pendidikan Fisika, 2024)
This research is based on the low physics learning outcomes of senior high school students. This study aims to increase students' motivation and learning outcomes using Orang Kayo Hitam Comic in physics learning. The comic used for this study is based on a folktale from Jambi Province entitled Orang Kayo Hitam. The study was conducted at SMA Negeri 9 Kota Jambi, grade 10, in 2022. This kind of study is Classroom Action Research (CAR), and it is divided into three cycles. The planning, implementation, observation, and reflection stages are the four phases that make up each cycle. Based on the study results, 44% of the first cycle's students achieved the minimum qualifying score (KKM). In the second cycle, it was 56%, and in the third, it became 78%. The N-gain value of 0.4 indicates that the increase in student motivation is moderate. According to the study's findings, using Orang Kayo Hitam comic can enhance students' motivation and their learning outcomes.